Children’s fiction books with augmented reality: assessment and foresight of a publishing phenomenon - Arellano-Yanguas, Villar (Revista General de Información y Documentación, 2025)
The integration of augmented reality (AR) technology in children’s books has represented one of the most promising publishing innovations of the past few decades. Incorporating multimodal digital content, which appears when readers overlap a mobile phone or tablet with specific pages, broadens the expressive possibilities of publications and can encourage reading motivation without losing direct contact with the physical book. This paper analyzes the Spanish experience with these publications, focusing on the corpus of children’s fiction works with AR; the aim is to determine the social impact of the phenomenon and the publishing sector’s assessment. To this end, the research adopts an ethnographic perspective, combining qualitative (interviews) and quantitative techniques (record counting). The results confirm a decreasing trend in the annual publication of AR books. Moreover, although the study shows the presence of the corpus in public libraries and bookstores, there is a general lack of awareness of these publications and limited attention in recommendation spaces. Publishers negatively assess the commercial results, but consider the professional experience as an enriching challenge. Looking ahead, and among the possible conditions for publishing books with AR, the importance of digital content which provides real added value to children’s works is emphasized. Other conclusions are the need to strengthen editorial teams with new creative profiles, develop collaboration strategies for promoting AR books, and enhance teacher training in reading innovations.